Analisis Usahatani Padi Organik Kelompok Tani Ciawitali Cilawu Garut - Tatang Mulyana; Mutia Salsabila; Asep Permadi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
Organik Pady is a superior food crop commodity in Cilawu District, Garut Regency. This study aims to analyze Organik Pady farming based on land tenure status. This research was conducted in Mangkurayat Village, Cilawu District, Garut Regency from October to November 2021. The types of data used in this study were primary data and secondary data. Sampling in this study using purposive sampling method. In order to obtain a sample of 20 people owner farmer, and 10 people of share tenant. Data analysis used in this research is descriptive quantitative by analizing farm production costs, revenue, income, and farming feasibility. The results showed that the average total production cost incurred by the owner farmer were Rp. 13.793486 /Ha/Planting Season, while the share tenant are Rp. 9.299.249 /Ha/Planting Season. The profit-sharing system for shelled corn farming in the research area for share tenant is 50% of the total yield of production. The shelled corn farming which is run by the owner farmers and share tenant is feasible to be cultivated with an average r/c ratio of 1,7 for the owner farmers, and the r/c ratio value of 1,2 for the share tenant. Â